The development of racquet speed - Elliott, B. (Medicine and Science in Tennis, 2003)
Tennis scientists are continually asked by players to develop techniques that permit more power, while those involved more with the medical aspect of the game are forced to develop better preventative programs and rehabilitative treatments to meet the demands placed on the body from movements associated with this additional power. There are several elements that contribute to an increase in racquet and therefore ball speed: